American Horror Fiction
IX, 180 p.
Keywords: This volume offers critical and theoretical perspectives on a genre which has remained popular for nearly two hundred years: American horror fiction. There are essays on Charles Brockden Brown, Edgar Allan Poe, H.P.Lovecraft, William Faulkner, Robert Bloch, Patricia Highsmith, Shirley Jackson, Stephen King and Suzy McKee Charnas, covering the period from 1798 to 1983. Each essay deals with a major figure in the genre, from Gothic orginators to modern feminist reworkings. A variety of reading strategies are employed to interrogate these texts, with feminist and psychoanalytic approaches well represented. These essays illustrate the fact that modern literary theory can usefully be applied to any text or genre. Students of horror fiction seeking new readings, and readers interested in modern approaches to literature, will find this book useful and informative. The essays are all new, and have been specially written for Insights by leading academics.